2008
DOI: 10.1210/jc.2007-2287
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ContinuousVersusCyclical Oral Contraception: A Randomized Controlled Trial

Abstract: Continuous oral contraception does not result in a reduction of bleeding days over a 168-d period of observation but provides greater suppression of the ovary and endometrium. These effects are associated with improved patient symptomatology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 39 publications
3
61
3
Order By: Relevance
“…Therefore, more long-term multicentre studies should be performed, with careful selection of the phenotype. Finally, there is some evidence that extended-cycle EPs (vs cyclic therapy) may offer greater hormonal suppression and prevent rebound ovarian function during the pill-free interval (102). However, their efficacy in the treatment of hirsutism should be investigated.…”
Section: Normal Weight Hirsute Women With Pcosmentioning
confidence: 99%
“…Therefore, more long-term multicentre studies should be performed, with careful selection of the phenotype. Finally, there is some evidence that extended-cycle EPs (vs cyclic therapy) may offer greater hormonal suppression and prevent rebound ovarian function during the pill-free interval (102). However, their efficacy in the treatment of hirsutism should be investigated.…”
Section: Normal Weight Hirsute Women With Pcosmentioning
confidence: 99%
“…These differences approached statistical significance (p-value = 0.054), but there were no pregnancies in either group. 21 In another study (n = 641), with a continuous OC regimen compared to a cyclic OC product, one woman became pregnant on continuous OC compared to three pregnancies in the cyclic comparator group, but the significance of this difference is not clear. 22 A study (n = 1 417) was also done to compare the contraceptive efficacy, cycle control, compliance and safety of a weekly transdermal contraceptive patch and a daily OC.…”
Section: Day 28mentioning
confidence: 99%
“…Patient satisfaction outcomes with regard to hormone withdrawal symptoms have been examined in extended-cycle regimens and are generally positive, with a number of studies reporting improvement in premenstrual symptoms and reduced headache 13,[43][44][45] . The Cochrane Review commented that extended-cycle regimens were better than traditional regimens in managing withdrawal New combined oral contraceptive pill regimens Read headache, genital irritation, tiredness, bloating, and menstrual pain 30 .…”
Section: Hormone Withdrawal Symptomsmentioning
confidence: 99%
“…This and other studies concluded that the degree of residual ovarian activity could be regarded as a useful measure of the effectiveness of oral contraceptives 51 . The scoring system combines ultrasound assessment of follicular size and appearance with the measurement of LH, FSH, oestradiol and progesterone levels 9,18,45 . A fascinating study into the question of missed pills and poor compliance randomised women to either a 21/7-or a 24/4 days-regimen of pills containing 20 mg EE and 3mg DRSP.…”
Section: What About Efficacy?mentioning
confidence: 99%